A Narrative Review on Microbial Biofilm Formation in Septicaemia due to Gram-negative Bacteria: A Cause of Concern - Akoijam Nisha Devi; Gargi Mudey; Dipika Shaw; Shahin Vishani; Anjali Patond (Journal of Clinical and Diagnostic Research)
Septicaemia, or bloodstream infection, is a serious condition associated with high morbidity and mortality. Gram-negative bacteria, particularly Enterobacterales, are the primary causative agents of septicaemia. Globally, there is an increasing prevalence of antibiotic-resistant gram-negative bacteria reported in bloodstream infections. One of the major mechanisms of antibiotic resistance in gram-negative bacteria is their ability to form biofilms. Biofilms facilitate the transfer of Antimicrobial Resistance (AMR) genes among the bacteria present within the biofilm. Biofilm formation poses a challenge for treatment management; additionally, biofilms protect the bacteria from antibiotics and the host immune response, thus helping the organisms to establish resistance to antibiotic agents. To date, no conclusive strategies or appropriate agents are available to combat bacteria in microbial biofilms formed inside the human host. The best way to fight biofilm-forming bacteria is to prevent infection and eradicate it before biofilms are formed by following proper preventive measures and using appropriate antibiotics. This review article aims to help readers understand the complex relationship between biofilm-forming ability and AMR among gram-negative bacteria causing septicaemia. Furthermore, the review explores the impact of biofilm formation on the pathogenesis of septicaemia and discusses strategies and agents to prevent and combat biofilm formation.